Deep Convection in the Labrador Sea: Moorings, Hydrography and Laboratory Simulations - Rhines, Peter B (1999)
The intensive resources directed at numerical models of the ocean need to be balanced by direct observation, theory and laboratory simulation. By applying these methods to some of the most complex parts of the ocean system, we hope to improve understanding of the total system. The convection and wind-driven activity of the upper ocean provide such a challenge, and in addition are particularly significant to problems of air/sea interaction, upper-ocean dynamics and dynamics of coastal seas. At high latitudes, convection reaches great depth, and influences the global general circulation.